Determining materials for energy conversion across scales: The alkaline oxygen evolution reaction - Philipp Gerschel; Steven Angel; Mohaned Hammad; André Olean‐Oliveira; Blaž Toplak; Vimanshu Chanda; Ricardo Martínez‐Hincapié; Sebastian Sanden; Ali Raza Khan; Da Xing; Amin Said Amin; Hartmut Wiggers; et al. (Carbon Energy)
Abstract Despite considerable efforts to develop electrolyzers for energy conversion, progress has been hindered during the implementation stage by different catalyst development requirements in academic and industrial research. Herein, a coherent workflow for the efficient transition of electrocatalysts from basic research to application readiness for the alkaline oxygen evolution reaction is proposed. To demonstrate this research approach, La0.8Sr0.2CoO3 is selected as a catalyst, and its electrocatalytic performance is compared with that of the benchmark material NiFe2O4. The La0.8Sr0.2CoO3 catalyst with the desired dispersity is successfully synthesized by scalable spray‐flame synthesis. Subsequently, inks are formulated using different binders (Nafion®, Naf; Sustainion®, Sus), and nickel substrates are spray coated, ensuring a homogeneous catalyst distribution. Extensive electrochemical evaluations, including several scale‐bridging techniques, highlight the efficiency of the La0.8Sr0.2CoO3 catalyst. Experiments using the scanning droplet cell (SDC) indicate good lateral homogeneity for La0.8Sr0.2CoO3 electrodes and NiFe2O4‐Sus, while the NiFe2O4‐Naf film suffers from delamination. Among the various half‐cell techniques, SDC proves to be a valuable tool to quickly check whether a catalyst layer is suitable for full‐cell‐level testing and will be used for the fast‐tracking of catalysts in the future. Complementary compression and flow cell experiments provide valuable information on the electrodes' behavior upon exposure to chemical and mechanical stress. Finally, parameters and conditions simulating industrial settings are applied using a zero‐gap cell. Findings from various research fields across different scales obtained based on the developed coherent workflow contribute to a better understanding of the electrocatalytic system at the early stages of development and provide important insights for the evaluation of novel materials that are to be used in large‐scale industrial applications.